A method for the extraction of shorelines from airborne lidar data in muddy areas and areas with shoals. Issue 5 (4th May 2022) - Li, Weihua; Liu, Hao; Qin, Changcai
ABSTRACT: The shoreline is an extremely important geographical element in marine management and construction, and accurate determination of its position has become a critical requirement for social development. Shoreline extraction is typically achieved through elevation recursion from a digital elevation model (DEM) generated from lidar data. However, analysis focusing on different shoreline types is limited. Furthermore, the elevation recursion algorithm is not unified and cannot be adapted to every type of shoreline. This study analysed the characteristics of shoreline data in shoal and muddy areas and proposed a new method for high-precision shoreline extraction from original lidar data. In this study, the accuracy evaluation indicators have also been designed to compare the shoreline extracted using the proposed method, to that produced by the contour tracking method. The experiments demonstrated that the method proposed in this paper can more accurately locate the shoreline and recreate its position and shape more closely than the contour tracking method. The results exhibited a decrease in the average error of points from 1 m to 0.5 m, and in the overall standard deviation of the shoreline from 0.2116 m to 0.1656 m.